Prūsų kalbos sudurtinių daiktavardžių kilmės klausimu - Lašinytė, Benita (Baltistica, 2007)
ON THE ORIGIN OF THE NOUN COMPOUNDS IN OLD PRUSSIANThe article deals with the origin of the noun compounds of the Elbing Vocabulary and the Third Catechism. It establishes that more than a half of the noun compounds of the Elbing Vocabulary and only three noun compounds of the Third Catechism are of Old Prussian origin. The remaining compounds of the Elbing Vocabulary and the majority of those in the Third Catechism are loan translations from German.The noun compounds of the Elbing Vocabulary obviously tend to have simple base words. Except for a few questionable examples, there are no case compounds in the Elbing Vocabulary – all of them may be termed as stem compounds. However the compounds of the Third Catechism follow a clear trend of being comprised of underlying derivatives as well as having a case form for the first constituent.The German influence on the compounds of the Elbing Vocabulary is not very strong – it has impacted it only on the lexical level, while the compounds of the Third Catechism have also undergone more radical changes on the structural level.According to the above-mentioned features, it can be stated that the noun compounds of the Elbing Vocabulary resemble Lithuanian ones, while those of the Third Catechism show similarities with Latvian compounds which are influenced by German to a fairly large extent.
Keywords: prūsų kalba; sudurtinis daiktavardis